Were the manufacturing companies resilient in the face of COVID-19 or did they take advantage? - Sabău-Popa, Claudia Diana; Rus, Luminita; Florea, Adrian; Ban, Olimpia-Iuliana; Dzitac, Simona; Marcu, Olivia Andreea (Technological and Economic Development of Economy, 2024)
The research paper aims to build a composite index of the financial performance of companies, to find if the impact of the COVID-19 crisis was significantly positive for most manufacturing companies listed on Bucharest Stock Exchange, and to look if the manufacturing companies were resilient being prepared with savings that could have mitigate the effects of this pandemic crisis. The results of the FE model selected show that 31.67% of the company’s equity variation is justified by the two independent variables, the stronger correlation of equity being with reserves. Based on the composite index of financial performance built, the manufacturing companies were grouped in three clusters: a cluster with low financial performance companies (z < 4), a cluster with good financial performance companies (4 ≤ z ≤ 8) and a cluster with high financial performance companies (z > 8). The third cluster groups the most analysed companies, on which the pandemic crisis had a positive impact, which achieved the highest financial performance; they are those companies that “take advantage” from the COVID-19 crisis, adapting their business strategy to the market conditions imposed. The article adds value to the specialty literature by building the financial performance’s composite indicator, clustering the manufacturing companies by financial performance’ Z-score.